Effect Ultrafiltration Rate On Blood Pressure Chronic Kidney Disease Patient During Hemodyalisis: A Literature Review - Nuriya, Nuriya; Taufik, Agis (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Introduction: Data from the Kidney Foundation Diatrans Indonesia stated that the number of patients with renal failure in Indonesia is estimated to increase 4,400 patients each year. One of the adverse effects of chronic kidney disease is the disorder of blood filtration. Interventions applicable to patients with impaired filtration include hemodialysis therapy. Complications that often occur in patients undergoing hemodialysis are hemodynamic disorders, especially blood pressure to drop or intradialytic hypotension. Objective: This study aims to review some literature on the effect of ultrafiltration rate on blood pressure of patients with chronic kidney disease who undergo hemodialysis. Method: Journal article search is done electronically using multiple databases: PubMed database, Google Scholar, Science Direct and Mendeley from January 2007 to November 2017. Keywords used were